Association of cigarette smoking and microRNA expression in rectal cancer: Insight into tumor phenotype. (December 2016) - Mullany, Lila E.; Herrick, Jennifer S.; Wolff, Roger K.; Stevens, John R.; Slattery, Martha L.
Highlights: Certain miRNAs were differentially expressed across only one smoking variable while others were across all three variables. Certain miRNAs were associated with both C/F/N smoking and CIMP High/MSI, which was also associated with C/F/N smoking. Smoking, as a lifestyle variable, may alter miRNA expression in rectal cancer, which in turn may influence tumor phenotype. Abstract: Smoking is known to influence messenger RNA (mRNA) expression in colorectal cancer (CRC) cases. As microRNAs (miRNAs) are known repressors of mRNAs, we hypothesize that smoking may influence miRNA expression, thus altering mRNA expression. Our sample consisted of 1447 CRC cases that had normal colorectal mucosa and carcinoma miRNA data and lifestyle data. We examined current smoking, current versus never and former versus never (C/F/N) smoking 1, and pack-years smoked with miRNA expression in normal mucosa as well as differential miRNA expression between paired normal and carcinoma tissue for colon and rectal tissue to determine associations between smoking and miRNA expression. We adjusted for multiple comparisons using the Benjamini Hochberg false discovery rate (FDR). Significant associations were seen for rectal differential miRNA expression only. We analyzed miRNAs significantly associated with smoking with CIMP and MSI status, using a polytomous logistic regression. Two hundred and thirty-one miRNAs were differentially expressed with current smoking, 172 with C/F/N, and 206 with pack-years smoked; 111 were associated with all three. Forty-three miRNAs were unique to current smoking, 14 were unique to C/F/N and 57 were unique to pack years smoked. Of the 306 unique miRNAs associated with cigarette smoking, 41 were inversely associated and 200 were directly associated with CIMP high or MSI tumor molecular phenotype for either colon or rectal cancer. Our results suggest that cigarette smoking can alter miRNA expression and, given associations with CIMP high and MSI tumor molecular phenotype, it is possible that smoking influences tumor phenotype through altered miRNA expression.